An Android based new German eID solution for policy making processes. Issue 11 (11th January 2016) - Rebahi, Yacine; Khalil, Mateusz; Hohberg, Simon; Lorenz, Pascal
Abstract: In the current paper, we propose a novel mobile‐based architecture that enforces security and privacy protection in the context of mParticipation. This architecture enables the citizens to cast their opinions anonymously and without limitation in time and space. It also removes the burden of preceding registration before any voting process. As the new electronic identity (eID) Cards are replacing the conventional identity cards in most European countries, we also discussed, in this paper, how the new German eID cards can be utilized for mobile participation. The use of the eID cards offers better flexibility and stronger security. A prototype implementation of this architecture is also described in this document, and the related performance is discussed. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Design and development of a novel mobile‐based opinion casting solution enable citizens, without limitation in time and space, to participate to policy making processes, while their privacy is protected, and their anonymity is ensured. This solution supports both general IdPs such as OpenSSO and OpenID as well as the new European eID cards.